Anticancer Mechanism of Astragalus Polysaccharide and Its Application in Cancer Immunotherapy - Ziqing He; Xiyu Liu; Simin Qin; Qun Yang; Jintong Na; Zhigang Xue; Liping Zhong (Pharmaceuticals, 2024)
Astragalus polysaccharide (APS) derived from A. membranaceus plays a crucial role in traditional Chinese medicine. These polysaccharides have shown antitumor effects and are considered safe. Thus, they have become increasingly important in cancer immunotherapy. APS can limit the spread of cancer by influencing immune cells, promoting cell death, triggering cancer cell autophagy, and impacting the tumor microenvironment. When used in combination with other therapies, APS can enhance treatment outcomes and reduce toxicity and side effects. APS combined with immune checkpoint inhibitors, relay cellular immunotherapy, and cancer vaccines have broadened the application of cancer immunotherapy and enhanced treatment effectiveness. By summarizing the research on APS in cancer immunotherapy over the past two decades, this review elaborates on the anticancer mechanism of APS and its use in cancer immunotherapy and clinical trials. Considering the multiple roles of APS, this review emphasizes the importance of using APS as an adjunct to cancer immunotherapy and compares other polysaccharides with APS. This discussion provides insights into the specific mechanism of action of APS, reveals the molecular targets of APS for developing effective clinical strategies, and highlights the wide application of APS in clinical cancer therapy in the future.